Associations of postmenopausal hormone therapy with metabolic syndrome among diabetic and non-diabetic women. (March 2019) - Kim, Ji-Eun; Choi, Jaesung; Park, JooYong; Lee, Jong-koo; Shin, Aesun; Park, Sang Min; Kang, Daehee; Choi, Ji-Yeob
Highlights: Hormone therapy (HT) use was associated with metabolic syndrome (MetS) components among both diabetic and non-diabetic postmenopausal women. 'Ever' use of hormone therapy was negatively associated with the prevalence of metabolic syndrome among non-diabetic women, and current users of hormone therapy had a lower prevalence of metabolic syndrome than current non-users. Although a longer duration of hormone therapy was associated with a decreasing prevalence of metabolic syndrome, there were no differential associations by age group. There was no differential association of hormone therapy with components of the metabolic syndrome by diabetes status; however, we could not totally exclude the healthy-user bias. Abstract: A lack of estrogen due to menopause changes metabolic homeostasis, which increases the risk of metabolic syndrome (MetS) in postmenopausal women. Hormone therapy (HT) has beneficial effects on chronic diseases as well as on menopause symptoms. The aim of this study was to investigate the association of HT use with MetS and its components by diabetes status in middle-aged postmenopausal Korean women. A cross-sectional analysis was undertaken of a total of 39, 295 non-diabetic and 3, 359 diabetic postmenopausal women aged 40 to 69 years from the Health Examinees-Gem (HEXA-G) study (2004–2013). The mean differences in the MetS components by HT use were assessed using a general linear model and Tukey's multiple comparisons tests. The prevalence odds ratio (POR) and 95% confidence intervals (CIs) were estimated using the logistic regression model. HT use was associated with lower fasting glucose level, total cholesterol, systolic blood pressure, body mass index, waist circumference, and waist-to-hip ratio among both diabetic and non-diabetic women. In non-diabetic women, HT 'ever' use was negatively associated with the prevalence of MetS (POR = 0.80, 95% CI: 0.75-0.85), and current users had a lower prevalence of MetS (POR = 0.68, 95% CI: 0.60-0.76). A longer duration of HT use was associated with a decreasing prevalence of MetS. We did not find heterogeneity by age regarding MetS prevalence. Our results suggest that HT use is negatively associated with the prevalence of MetS among postmenopausal women. However, further longitudinal studies are required to investigate the effect of HT on MetS in Korean women.